PENDEKATAN SISTEM MANAJEMEN MUTU DALAM PENDIDIKAN KEJURUAN: SYSTEMATIC LITERATURE REVIEW MENGGUNAKAN PRISMA DAN IMPLIKASINYA BAGI SMK NEGERI 1 KONGBENG KABUPATEN KUTAI TIMUR - Bambang Setiono; Supriadi; Yustina Romaida Efrianti BR Situmorang; Azainil; Laili Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of research on quality management systems in education, identify the factors influencing successful implementation, and examine their implications for vocational school management. The study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Literature searches were conducted through Scopus, Web of Science, ERIC, Dimensions, Google Scholar, and Crossref databases, covering publications from 2020 to 2025. The initial search identified 486 articles. After duplicate removal, screening, and eligibility assessment, 58 articles met the inclusion criteria and were analyzed. The findings indicate that quality management systems contribute significantly to improving educational service quality, school management effectiveness, stakeholder satisfaction, human resource performance, and student achievement. The most influential factors affecting successful implementation include leadership, quality culture, human resource competence, information technology utilization, stakeholder involvement, and continuous evaluation. The study demonstrates that an integrated quality management system strengthens school governance and enhances institutional competitiveness. The findings provide a conceptual foundation for the development of quality management systems at SMK Negeri 1 Kongbeng, Kutai Timur Regency, to support sustainable and high-quality vocational education.